Economic existence of home industry worker families in a positive law perspective - Muamar, Afif; Nurkhaerani, Ema; Inayah, Iin (IAIN Syekh Nurjati Cirebon, 2024)
The employment absorption by the Sukarasa Keripik Kaca home industry in Tenjolaya Hamlet, Kertayasa Village, Cijulang District, Pangandaran Regency needs to be further examined from the perspective of positive law. The aim is to understand the existence of the Sukarasa Keripik Kaca home industry in absorbing local labor and to review the positive legal perspective on the employment absorption system in enhancing community income in Kertayasa Village, Cijulang District, Pangandaran Regency. This research is classified as qualitative research, and the data collection techniques used were interviews, observation, and documentation. The research results show that the Sukarasa Keripik Kaca home industry continues to operate to this day. A total of 8 workers have been absorbed. Based on the review of Law Number 13 of 2003 concerning Manpower, the employment absorption system is appropriate as there is no discriminatory treatment. The application of the Regional Minimum Wage applies to companies with a minimum of 20 workers. Since the Sukarasa Keripik Kaca home industry only has 8 workers, the wages provided are appropriate.Keywords: Family Economy, Home Industry, Sukarasa Keripik Kaca, Positive Law.